Adhesion Properties of Human Oral Epithelial‐Derived Cells to Zirconia. (5th August 2015) - Okabe, Eijiro; Ishihara, Yuichi; Kikuchi, Takeshi; Izawa, Ario; Kobayashi, Shuichiro; Goto, Hisashi; Kamiya, Yosuke; Sasaki, Keisuke; Ban, Seiji; Noguchi, Toshihide; Kawai, Tatsushi; Mitani, Akio
Abstract: Background: Few studies have examined epithelial attachment to zirconia and the proliferative ability of epithelial cells on zirconia surfaces. Purpose: To evaluate the adhesion properties of zirconia materials for epithelial cell attachment and compare this with titanium and alumina. Materials and Methods: Human oral epithelial cells were cultured on smooth‐surfaced specimens of commercially pure titanium (cpTi), ceria‐stabilized zirconia/alumina nano‐composite (P‐NANOZR), yttria‐stabilized zirconia (Cercon), and alumina oxide (inCoris AL). The cell morphology, the cell viability and mRNA of integrin β4, laminin γ2, catenin δ2, and E‐cadherin were evaluated by SEM, Cell‐Counting Kit‐8, and real‐time PCR, respectively. Results: Morphology of cells attached to specimens was similar among all groups. The viable cell numbers on Cercon and inCoris AL after 24 hours culture were significantly higher than for cpTi. Integrin β4, laminin γ2, and catenin δ2 mRNA expression was not different among all groups. However, at 3 and 24 hours after incubation, E‐cadherin mRNA expression in the P‐NANOZR group was significantly higher than for cpTi. Conclusion: Zirconia may support binding of epithelial cells through hemidesmosomes comparable with titanium. Furthermore, P‐NANOZR may impart resistance to exogenous stimuli through strong intercellular contacts with peri‐implant mucosal cells when used as an abutment and implant superstructure.